The Impact of Mentoring Strategy on Speaking Skills of English Education Study Program - Bayu Prasetyo; Restu Arini (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study investigates the impact of mentoring as a teaching strategy toward students’ speaking skill. The participants of this study were 24 students of English Education Study Program in a private university in Yogyakarta. A mixed-method was used in the study. The instruments to obtain the data were test and interview. The quantitative analysis revealed an improvement in students’ test score, while qualitative data from interviews provided insights into students’ perceptions and experiences with mentoring. The result shows an improvement on the speaking skills in the mean score from 2.77 to 3.18. It indicates that mentoring strategy positively impacted students’ speaking skill, particularly on the aspect of accuracy, fluency, and vocabulary. The interview also resulted in positive perception of the students in increasing students’ confidence and critical thinking.